The new era of diabetes management: Comprehensive benefits of Ozempic in diabetes and co-morbidities (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
The global health landscape is increasingly burdened by the rising prevalence of chronic conditions such as Type 2 Diabetes (T2D), obesity, cardiovascular disease (CVD), and chronic kidney disease (CKD), which are often interlinked through underlying metabolic dysfunction. This presentation provides an in-depth exploration of the multifaceted benefits of Ozempic (Semaglutide), a glucagon-like peptide-1 receptor agonist (GLP-1RA), as a cornerstone treatment for managing T2D and its associated comorbidities. Comorbidities like metabolic dysfunction-associated steatohepatitis (MASH) and cardiovascular complications are prevalent, underscoring the necessity of integrated treatment approaches.Clinical trial data from pivotal studies, such as the SUSTAIN and FLOW trials, evidenced remarkable outcomes, including up to 80% of patients achieving their HbA1c target of